Combination effects of DNase I and tobramycin on survival and biofilm architectures of Pseudomonas aeruginosa and Klebsiella pneumoniae isolated from chronic rhinosinusitis patients - Chitchanok Anutrakunchai; Saharut Wongkaewkhiaw; Sakawrat Kanthawong; Sorujsiri Chareonsudjai; Rattiyaphorn Pakkulnan; Suwimol Taweechaisupapong (Songklanakarin Journal of Science and Technology (SJST), 2022)
This study aimed to investigate the effects of DNase I in combination with tobramycin (TOB) on drug susceptibility and biofilm architectures of Pseudomonas aeruginosa and Klebsiella pneumoniae. Biofilm formation, eDNA production and drug susceptibilities of P. aeruginosa and K. pneumoniae in both planktonic and biofilm forms were evaluated under different nutrient concentrations. The biofilm architectures of both bacteria were evaluated using confocal laser scanning microscopy. The results showed that the biofilm formations and eDNA quantities of both bacteria were reduced in a nutrient-limited condition. The eDNA concentrations in the biofilms were correlated with the amount of biofilm formed. Moreover, a combination with DNase I can enhance the bactericidal activity of TOB and decrease biofilm formation of both bacteria compared with TOB alone. These results suggest that the combined effects of DNase I and TOB allows prevention of biofilm formation and subsequent penetration of the drug resulting in an increased anti-biofilm effect.